Characteristics of ventricular tachyarrhythmias and their susceptibility to antitachycardia pacing termination in patients with ischemic and nonischemic cardiomyopathy: A patient‐level meta‐analysis of three large clinical trials. (28th July 2020) - Cheng, Alan; Joung, Boyoung; Brown, Mark L.; Koehler, Jodi; Lexcen, Daniel R.; Sanders, Prashanthan; Ellenbogen, Kenneth A.
Abstract: Background: Implantable cardioverter defibrillators (ICDs) reduce all‐cause mortality among cardiomyopathy patients. Whether or not antitachycardia pacing (ATP) is equally effective in ischemic (ICM) and nonischemic (NICM) cardiomyopathy patients remains poorly understood. We describe the distribution of monomorphic (MVT) and non‐monomorphic (polymorphic ventricular tachycardia/ventricular fibrillation [PVT/VF]) ventricular tachyarrhythmias among ICM and NICM primary prevention patients. Methods: This patient‐level meta‐analysis included primary prevention patients from the Shock‐Less ( n = 3519), PainFree SST ( n = 1917), and PREPARE ( n = 690) studies. Distribution of MVT and PVT/VF events were compared with χ 2 tests. ATP success was estimated using a generalized estimating equation model to correct for multiple episodes for a patient between cohorts for slow (≥320 ms) and fast (240–310 ms) MVTs. Results: Among 6126 patients, 714 (29% NICM, age 66 ± 13 years, female 18%, EF = 29 ± 12%) had a total of 4444 treated ventricular tachyarrhythmia episodes. The rate of individuals treated for MVT or PVT/VF was comparable between ICM (11.9%) and NICM (11.2%) over 21 ± 10 months. In addition, the distribution of MVT (76% ICM vs. 71% NICM) and PVT/VF (15% ICM vs. 20% NICM) was not significantly different ( p = .28). Among MVT episodes, the average tachycardia cycle lengths (332 ± 58 ms ICM vs. 313 ± 40 ms NICM; p = .27) were similar, as was the likelihood of ATP‐associated termination (74.6% ICM vs. 76.4% NICM; p = .58). Overall, ATP success was higher for slow (≥320 ms) MVT versus faster (240–310 ms) episodes (84.1% vs. 69%; p < .001). Conclusion: In a large cohort of primary prevention ICD patients, ICM and NICM patients have similar rates and proportions of MVT and PVT/VF episodes. ATP‐associated termination of MVT was comparable between the two groups.